Avaliação do Projeto Inclusão Digital do Programa Espaço Nordeste do Banco do Nordeste - Araújo, Zena Cleide Lobo Galvão (2014)
This paper discusses how central theme the Evaluation of Digital Inclusion Public Policy. In this context, I propose as an object of study, evaluate the Digital Inclusion Project Pedro II, funded by the Nordeste- BN Bank, implemented by the Northeast Institute Citizenship - INEC and developed in the Northeast Area. This is a Digital Inclusion strategy deployed and implemented in the municipality of Pedro II, belonging to the State of Piauí, which provide access to the monitored IT infrastructure of a pedagogical proposal, which, based on six stages, in order to implement a digital culture for young people in the municipality reference. This research aims to evaluate the effectiveness of the Digital Inclusion Project Pedro II, ascertaining to what extent was managing to promote digital inclusion of its users. To assess the effectiveness of design research, we will use the evaluative perspective sociodigital effectiveness, anchored by Mark Warschauer, when the standing offer, continuous viability and use of physical evaluative dimensions, digital, human and social, as key inputs for effective project digital inclusion. In this perspective, to carry out the research study, I intend to make an assessment of effectiveness of the Digital Inclusion Project Pedro II, not limited only to assess about the objectives, targets and or results. The proposal is to work with the notion of sociodigital effectiveness as an evaluative dimension for verifying the digital inclusion in their local and social context, considering that this will only be achieved to the extent that there is effectiveness sociodigital. To achieve this purpose, giving priority to qualitative research will be used, without neglecting the figures, Northeast Pedro II space, focusing on the case study, using ethnography as a reference in the data analysis. I will use as main research instruments the documentary survey, literature and field research, the data collection will be through interviews and questionnaires from post-constructivist approach Raul Lejano (2006). Given the above, I conclude that the assessment made on the effectiveness of Digital Inclusion Project Pedro II in the evaluative perspective of sociodigital effectiveness, anchored by Mark Warschauer, using as analytical reference the physical evaluative dimensions, digital, human and social, NOT PROMOTE digital inclusion of its users.